Search for blocks/addresses/...

Proofgold Asset

asset id
7e4e1f418d08fb9da31789177c21038ab401e0d1abef78555f93c7d49d4f4445
asset hash
b34e567bdd80a53b2f29ab7911f799319585244531f04749cdff56fd301bdbbd
bday / block
27058
tx
d0e45..
preasset
doc published by Pr5Zc..
Known 93eac.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 . x0 x2x0 x3x0 x4x0 x5x0 x6x1 x2 (x1 x3 (x1 x4 (x1 x5 x6))) = x1 x3 (x1 x4 (x1 x5 (x1 x2 x6)))
Known 16f0b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x5 (x1 x4 (x1 x7 (x1 x3 (x1 x6 (x1 x2 x9))))))
Theorem 2af44.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x8 (x1 x6 (x1 x2 x5))))))
...

Theorem 4a3ed.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x8 (x1 x6 (x1 x2 x5))))))
...

Known bb628.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x7 x9))))))
Theorem 5a654.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x2 (x1 x8 x5))))))
...

Theorem baaa9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x2 (x1 x8 x5))))))
...

Known 01f1a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x2 (x1 x5 x9))))))
Theorem c19a1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x2 (x1 x5 x8))))))
...

Theorem 9f590.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x2 (x1 x5 x8))))))
...

Known d2611.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x5 (x1 x4 (x1 x7 (x1 x6 (x1 x3 (x1 x2 x9))))))
Theorem e641c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x5 (x1 x2 x8))))))
...

Theorem f310f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x5 (x1 x2 x8))))))
...

Known 6f1df.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x5 (x1 x4 (x1 x6 (x1 x3 (x1 x7 (x1 x2 x9))))))
Theorem f6cc2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x8 (x1 x2 x5))))))
...

Theorem 23a81.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x6 (x1 x8 (x1 x2 x5))))))
...

Known 45f87.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 . x0 x2x0 x3x0 x4x0 x5x1 x2 (x1 x3 (x1 x4 x5)) = x1 x3 (x1 x4 (x1 x2 x5))
Theorem 09661.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x8 x6))))))
...

Theorem 74ec3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x8 x6))))))
...

Known 3656e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x6 x9))))))
Theorem 18d12.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x6 x8))))))
...

Theorem f39cf.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x2 (x1 x6 x8))))))
...

Known 5f60f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x5 (x1 x4 (x1 x6 (x1 x7 (x1 x3 (x1 x2 x9))))))
Theorem f966c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x6 (x1 x2 x8))))))
...

Theorem eb77f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x6 (x1 x2 x8))))))
...

Theorem a5542.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x8 (x1 x2 x6))))))
...

Theorem a5232.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x5 (x1 x8 (x1 x2 x6))))))
...

Known 67b34.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x7 x9))))))
Theorem 48ae5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x8 x6))))))
...

Theorem 76ff4.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x8 x6))))))
...

Known 39738.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x6 x9))))))
Theorem f0eab.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x6 x8))))))
...

Theorem 7d27d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x5 (x1 x6 x8))))))
...

Theorem f0e76.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x6 (x1 x8 x5))))))
...

Theorem 58764.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x6 (x1 x8 x5))))))
...

Known fa915.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x6 (x1 x5 x9))))))
Theorem 43c8f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x6 (x1 x5 x8))))))
...

Theorem 97847.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x6 (x1 x5 x8))))))
...

Known c4ba8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x7 (x1 x5 x9))))))
Theorem 3417a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x8 (x1 x6 x5))))))
...

Theorem fb2a9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x8 (x1 x6 x5))))))
...

Theorem d0ffe.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x8 (x1 x5 x6))))))
...

Theorem c1e0d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x3 (x1 x2 (x1 x8 (x1 x5 x6))))))
...

Known c0c54.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x2 x8)))))
Known 86e82.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x4 (x1 x7 (x1 x2 (x1 x5 x9))))))
Theorem 1b94b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x2 (x1 x6 x3))))))
...

Theorem 3b0c6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x2 (x1 x6 x3))))))
...

Known 3b3e5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x7 (x1 x2 (x1 x3 x9))))))
Theorem 1ba11.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x2 (x1 x3 x6))))))
...

Theorem ea208.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x2 (x1 x3 x6))))))
...

Known cbdc2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 (x1 x2 x9))))))
Theorem 32221.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x3 (x1 x6 x2))))))
...

Theorem 6b525.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x3 (x1 x6 x2))))))
...

Known 8ab2b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x7 (x1 x3 (x1 x2 x9))))))
Theorem 4872d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x3 (x1 x2 x6))))))
...

Theorem c71fe.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x3 (x1 x2 x6))))))
...

Known 20cf1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x4 (x1 x5 (x1 x7 (x1 x3 (x1 x6 (x1 x2 x9))))))
Theorem 24fc5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x6 (x1 x3 x2))))))
...

Theorem 38b61.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x6 (x1 x3 x2))))))
...

Theorem 368b5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x6 (x1 x2 x3))))))
...

Theorem ee8eb.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x8 (x1 x6 (x1 x2 x3))))))
...

Known 9d26e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x4 (x1 x5 (x1 x2 (x1 x7 x9))))))
Theorem 33b15.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x2 (x1 x8 x3))))))
...

Theorem 6b793.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x2 (x1 x8 x3))))))
...

Known ee67d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x2 (x1 x3 x9))))))
Theorem a6b91.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x2 (x1 x3 x8))))))
...

Theorem cc73d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x2 (x1 x3 x8))))))
...

Theorem a0640.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x8 x2))))))
...

Theorem 4d03b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x8 x2))))))
...

Known 22f31.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x2 x9))))))
Theorem e304f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x2 x8))))))
...

Theorem de468.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x2 x8))))))
...

Known 5d1f0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x4 (x1 x5 (x1 x6 (x1 x3 (x1 x7 (x1 x2 x9))))))
Theorem 7e590.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x8 (x1 x3 x2))))))
...

Theorem 867ed.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x8 (x1 x3 x2))))))
...

Theorem e7f48.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x8 (x1 x2 x3))))))
...

Theorem 3c549.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x6 (x1 x8 (x1 x2 x3))))))
...

Known c892a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x7 x9))))))
Theorem 2439d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x8 x6))))))
...

Theorem 99106.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x8 x6))))))
...

Known df364.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x6 x9))))))
Theorem 3cc9c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x6 x8))))))
...

Theorem 9e8c8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x6 x8))))))
...

Theorem 7156b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x6 (x1 x2 x8))))))
...

Theorem 7243f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x6 (x1 x2 x8))))))
...

Known c6997.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x3 (x1 x7 (x1 x2 x9))))))
Theorem b9644.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x8 (x1 x2 x6))))))
...

Theorem ede8c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x8 (x1 x2 x6))))))
...

Known 80189.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x7 x9))))))
Theorem 29aeb.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x8 x6))))))
...

Theorem e7e78.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x8 x6))))))
...

Known e7411.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x6 x9))))))
Theorem 247a7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x6 x8))))))
...

Theorem a045c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x6 x8))))))
...

Known 32a41.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x5 (x1 x7 x9))))))
Theorem 3b036.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x6 (x1 x8 x3))))))
...

Theorem d8d6c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x6 (x1 x8 x3))))))
...

Known d21d2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x6 (x1 x3 x9))))))
Theorem 54f9c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x6 (x1 x3 x8))))))
...

Theorem e89d3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x6 (x1 x3 x8))))))
...

Known 9a07e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x7 (x1 x5 x9))))))
Theorem 70c7d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x6 x3))))))
...

Theorem 588f5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x6 x3))))))
...

Known f23a6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x7 (x1 x3 x9))))))
Theorem 9613f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x3 x6))))))
...

Theorem 5a79d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x3 x6))))))
...

Known fdc4b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x5 (x1 x7 (x1 x2 (x1 x4 x9))))))
Theorem 90b15.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x2 (x1 x5 x3))))))
...

Theorem 1b269.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x2 (x1 x5 x3))))))
...

Theorem 31c99.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x2 (x1 x3 x5))))))
...

Theorem f0208.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x2 (x1 x3 x5))))))
...

Theorem f587a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x3 (x1 x5 x2))))))
...

Theorem 938e8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x3 (x1 x5 x2))))))
...

Theorem 7320a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x3 (x1 x2 x5))))))
...

Theorem d8966.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x3 (x1 x2 x5))))))
...

Known 20669.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x4 (x1 x7 (x1 x5 (x1 x3 (x1 x6 (x1 x2 x9))))))
Theorem f0a70.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x5 (x1 x3 x2))))))
...

Theorem 09fb7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x5 (x1 x3 x2))))))
...

Theorem 13c6a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x5 (x1 x2 x3))))))
...

Theorem a3763.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x8 (x1 x5 (x1 x2 x3))))))
...

Known 53ebd.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x3 (x1 x5 (x1 x4 (x1 x2 (x1 x7 x9))))))
Theorem a12b1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x2 (x1 x8 x3))))))
...

Theorem f54c5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x2 (x1 x8 x3))))))
...

Known 5a79a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x2 (x1 x3 x9))))))
Theorem 9786a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x2 (x1 x3 x8))))))
...

Theorem 00043.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x2 (x1 x3 x8))))))
...

Theorem 18091.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x8 x2))))))
...

Theorem 31cad.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x8 x2))))))
...

Known de53a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x2 x9))))))
Theorem 4fa1e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x2 x8))))))
...

Theorem 7e39e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x2 x8))))))
...

Known e79d3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x4 (x1 x6 (x1 x5 (x1 x3 (x1 x7 (x1 x2 x9))))))
Theorem 39fd1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x8 (x1 x3 x2))))))
...

Theorem cb701.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x8 (x1 x3 x2))))))
...

Theorem cc78a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x8 (x1 x2 x3))))))
...

Theorem c5861.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x5 (x1 x8 (x1 x2 x3))))))
...

Theorem 1ea65.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x8 x5))))))
...

Theorem d951b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x8 x5))))))
...

Known 31f67.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x9))))))
Theorem f5482.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x8))))))
...

Theorem 18d70.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x8))))))
...

Known c7ac9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x8 (x1 x6 (x1 x4 (x1 x7 (x1 x5 (x1 x3 (x1 x2 x9))))))
Theorem 8cdae.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x5 (x1 x2 x8))))))
...

Theorem aba66.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x5 (x1 x2 x8))))))
...

Theorem 4da8c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x8 (x1 x2 x5))))))
...

Theorem 73be3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x9 (x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x8 (x1 x2 x5))))))
...